Quantification of Contrast Kinetics in Clinical Imaging - Mischi, Massimo (Springer International Publishing, 2018)
This book provides a comprehensive survey of the pharmacokinetic models used for the quantitative interpretation of contrast-enhanced imaging. It discusses all the available imaging technologies and the problems related to the calibration of the imaging system and accuracy of the estimated physiological parameters. Enhancing imaging modalities using contrast agents has opened up new opportunities for going beyond morphological information and enabling minimally invasive assessment of tissue and organ functionality down to the molecular level. In combination with mathematical modeling of the contrast agent kinetics, contrast- enhanced imaging has the potential to provide clinically valuable additional information by estimating quantitative physiological parameters. The book presents the broad spectrum of diagnostic possibilities provided by quantitative contrast-enhanced imaging, with a particular focus on cardiology and oncology, as well as novel developments in the area of quantitative molecular imaging along with their potential clinical applications. Given the variety of available techniques, the choice of the appropriate imaging modality and the most suitable pharmacokinetic model is often challenging. As such, the book provides a valuable technical guide for researchers, clinical scientists, and experts in the field who wish to better understand and properly apply tracer-kinetic modeling for quantitative contrast-enhanced imaging.